Surgical Implications of Superior Thyroid Cornu Agenesis in Laryngeal Malignancy - Keshav Kumar Gupta; Zahir Mughal; Ijaz Ahmad (Turkish Archives of Otorhinolaryngology, 2022)

(untitled)
The most commonly reported superior thyroid cornu (STC) anatomical variation is in STC syndrome, where the cornu is enlarged or medially displaced. STC agenesis is a rare laryngeal variation that can be unilateral or bilateral. Previous studies have reported STC agenesis in cadaveric or forensic studies in patients with an otherwise normal larynx. We report a case of unilateral STC agenesis in the context of a stage III glottic laryngeal squamous cell carcinoma. The variation was discovered intra-operatively during a total laryngectomy and was clinically unknown beforehand. There were no clinical or histological signs of bony erosion by the tumor. To our knowledge, this is the first report of unilateral STC agenesis in a patient with laryngeal malignancy. This article draws attention to a rare anatomical variant of the larynx and highlights the surgical implications including potential diagnostic challenges and operative considerations.